2012
DOI: 10.1177/0269881112466183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antipsychotic treatment on cognition in healthy subjects

Abstract: Cognitive impairments can be observed in the majority of diseases with disturbed dopamine transmission. They are considered as core symptoms of schizophrenia, a disorder in which they appear to be particularly pronounced. Their neurobiological background is not yet sufficiently investigated, but dopaminergic systems are believed to play a crucial role. The aim of this single-blind, randomised, placebo-controlled study was to examine the effects of subchronic antidopaminergic treatment on cognitive functions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…More precisely, phasic dopamine transmission in response to a reward-predicting cue results in faster RTs (Satoh et al, 2003; Ko and Wanat, 2016), probably via innervating the NAcc (McGinty et al, 2013), which might serve as hub between reward related limbic signals and motor control circuits (Groenewegen et al, 1996). Therefore, movement initiation relies on a healthy dopaminergic system and, consequently, slower RTs have been shown in patients with Parkinson disease, who suffer from a massive loss of dopamine neurons (Mazzoni et al, 2007), during pharmacologically induced dopamine depletion in rats (Cole and Robbins, 1989), as well as in humans after D2 receptor blockage by haloperidol (Saeedi et al, 2006; Veselinović et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…More precisely, phasic dopamine transmission in response to a reward-predicting cue results in faster RTs (Satoh et al, 2003; Ko and Wanat, 2016), probably via innervating the NAcc (McGinty et al, 2013), which might serve as hub between reward related limbic signals and motor control circuits (Groenewegen et al, 1996). Therefore, movement initiation relies on a healthy dopaminergic system and, consequently, slower RTs have been shown in patients with Parkinson disease, who suffer from a massive loss of dopamine neurons (Mazzoni et al, 2007), during pharmacologically induced dopamine depletion in rats (Cole and Robbins, 1989), as well as in humans after D2 receptor blockage by haloperidol (Saeedi et al, 2006; Veselinović et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…As processing speed is important for the performance of higher cognitive operations, such as executive functions and memory, it has been suggested that impaired processing speed underlies the abnormalities in these areas (42). On the other hand, to complicate this further, a reduction of processing speed has also been found associated with antipsychotic medication (43). …”
Section: Discussionmentioning
confidence: 99%
“…Intactness of the functions of attention as prerequisite for effective behaviour in everyday life was assessed using the standardised computer test system “Test of Attentional Performance (TAP) 2.1” . The TAP has been developed in 1994 by Zimmermann & Fimm as an assessment of attention deficits in adults, and has since been validated and used as a reliable tool for attentional impairment in different trials . Within this procedure, simple reaction paradigms were chosen, in which participants had to react selectively to well discriminable, non verbal visual and acoustic stimuli by a simple motoric reaction (a simple keypress).…”
Section: Methodsmentioning
confidence: 99%